2019
DOI: 10.1109/tvt.2019.2918546
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Cellular Radio Access Networks Relying on Control- and User-Plane Separation

Abstract: In a cellular radio access network (RAN) relying on control-and user-plane separation, control base stations (CBSs) form the control plane (CP) and take care of control coverage as well as low speed data delivery. In contrast, traffic base stations (TBSs) in the user plane (UP) are used for transmitting high speed data. Based on queuing theory and stochastic geometry, we derive the coverage probability of the CP under non-line-ofsight (NLoS) transmissions, and derive the energy efficiency of the UP under coexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Yang et al [12] have shown that the CUPS architecture outperforms the conventional network architecture in terms of the coverage probability and the handover cost in UDNs. Liang et al [13] employed the stochastic geometry and queuing theory to analyze the coverage probability of the CP assuming nonline-of-sight (NLoS) transmissions and the energy efficiency of the UP under the co-existence of both NLoS and line-ofsight (LoS) transmissions.…”
Section: A Related Workmentioning
confidence: 99%
“…Yang et al [12] have shown that the CUPS architecture outperforms the conventional network architecture in terms of the coverage probability and the handover cost in UDNs. Liang et al [13] employed the stochastic geometry and queuing theory to analyze the coverage probability of the CP assuming nonline-of-sight (NLoS) transmissions and the energy efficiency of the UP under the co-existence of both NLoS and line-ofsight (LoS) transmissions.…”
Section: A Related Workmentioning
confidence: 99%
“…There was no comparison with the energy consumption of legacy system. Similarly, the recent paper [52] calculates and optimizes coverage probability of signaling BSs under non-line-of sight (NLoS) and energy efficiency of data BSs under LoS and NLoS conditions but did not compare the energy efficiency with that of a legacy system.…”
Section: Related Workmentioning
confidence: 99%
“…The utilization of a highfrequency band and shorter transmission distances in the U-plane introduces a more complex wireless environment, leading to the coexistence of line-of-sight (LoS) and non-lineof-sight (NLoS) transmissions. In this scenario, the SE, EE, and coverage have been analyzed in [11]. Additionally, the use of unlicensed bands in the U-plane has been explored in [12], [13].…”
Section: Introductionmentioning
confidence: 99%
“…Random service requests from users are aggregated at their associated BSs, and channels are allocated for data transfer. Queueing models have been applied to analyze the traffic conditions according to different network models, including M/M/1 [42], M/M/C/C [11], M/G/1 [43] and interacting queues [41], [44]. [45]- [47] adopt the mean-field approximation to settle the "interacting queue" problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation